1996
DOI: 10.1073/pnas.93.15.8095
|View full text |Cite
|
Sign up to set email alerts
|

The whistle and the rattle: the design of sound producing muscles.

Abstract: Vertebrate sound producing muscles often operate at frequencies exceeding 100 Hz, making them the fastest vertebrate muscles. Like other vertebrate muscle, these sonic muscles are "synchronous," necessitating that calcium be released and resequestered by the sarcoplasmic reticulum during each contraction cycle. Thus to operate at such high frequencies, vertebrate sonic muscles require extreme adaptations. We have found that to generate the "boatwhistle" mating call , the swimbladder muscle fibers of toadfish h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
230
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(243 citation statements)
references
References 34 publications
8
230
0
1
Order By: Relevance
“…Although only two catfish species were studied quantitatively, it is concluded that differences in the contraction frequency cannot be explained based on differences in the fine structural design of muscle fibers. Besides differences in the morphology of sonic organs, other differences between both families probably exist in the contraction kinetics of sonic muscle fibers, for example differences in speeds of calcium transients, crossbridge detachment rates, and probably kinetic off-rates of calcium from troponin (Rome et al, 1996).…”
Section: Fine Structure and Contraction Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Although only two catfish species were studied quantitatively, it is concluded that differences in the contraction frequency cannot be explained based on differences in the fine structural design of muscle fibers. Besides differences in the morphology of sonic organs, other differences between both families probably exist in the contraction kinetics of sonic muscle fibers, for example differences in speeds of calcium transients, crossbridge detachment rates, and probably kinetic off-rates of calcium from troponin (Rome et al, 1996).…”
Section: Fine Structure and Contraction Frequencymentioning
confidence: 99%
“…Contrary to locomotory muscles, drumming muscles possess thin myofibrils and an elaborate development of the sarcoplasmic reticulum (Fawcett and Revel, 1961;Eichelberg, 1977;Ono and Poss, 1981;Bass and Marchaterre, 1989;Fine et al, 1993;Loesser et al, 1997). These features are linked to an unusually rapid calcium cycling necessary for fibers to operate at such high frequencies (Appelt et al, 1991;Rome et al, 1996). Feher et al (1998) relate the extensive sarcoplasmic reticulum to calcium capacity, which allows the muscle to keep contracting even though calcium is not completely recycled.…”
mentioning
confidence: 99%
“…These results thus provide independent support for the premise that 'sonic muscles', those used in sound production, are among the fastest vertebrate muscles known. Specifically, the shaker muscles of a rattlesnake's rattle contract at ~90·Hz, several times faster than more normal vertebrate locomotory muscles, which contract at 20-30·Hz (Rome et al, 1996). The piprids described herein can employ similarly rapid wing cycles of 75·Hz (P. mentalis, rub-snap) and 80·Hz (Manacus, snort), at least doubling the contraction rates used in normal flight.…”
Section: Morphological and Physiological Significancementioning
confidence: 99%
“…Vocalizations are produced by the rapid contraction of paired striated muscles attached to the walls of the swimbladder (Fine et al, 2001;Fine et al, 2002), with ultrastructural traits divergent from trunk skeletal muscles (e.g. Bass and Marchaterre, 1989;Fawcett and Revel, 1961), that are adapted to contraction frequencies which are among the fastest of vertebrate skeletal muscles (Rome, 2006;Rome et al, 1996;Skoglund, 1961).…”
Section: Introductionmentioning
confidence: 99%